Protein- and Peptide-Based Biosensors in Artificial Olfaction - Barbosa, Arménio J. M. (2019)
info:eu-repo/grantAgreement/FCT/5876/147258/PT This work was supported by the European Research Council through the grant reference SCENT-ERC-2014-STG-639123 (2015-2020), and by the Unidade de Ciências Biomoleculares Aplicadas-UCIBIO, which is financed by national funds from FCT/MEC (UID/Multi/04378/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement ( POCI-01-0145-FEDER-007728 ). A.J.M. Barbosa and A.R. Oliveira thank fellowships SFRH/BPD/112543/2015 and SFRH/BD/128687/2017 from FCT/MCTES , Portugal.